Skin To Skin Contact pada BBLR terhadap Waktu, Durasi dan Dampaknya - Sitinjak, Eva Perawaty; Chodidjah, Siti; Rachmawati, Imami Nur (Journal of Telenursing (JOTING), 2024)
This research aims to examine the implementation of skin-to-skin contact for LBW, which includes an analysis of when it is fastest to start, how long it lasts, and what the impact is. The research method used was a systematic review through searches in electronic databases, namely Proquest, Scopus, EBSCOhost, Clinical Key, and Clinical Key for Nursing from 2013 to 2023. The study results showed that early skin-to-skin contact for LBW was safe from eight research articles. Starting in the first 24 hours of life, including mild to moderate unstable conditions, still using a breathing apparatus and IV line (umbilical or central). The initial duration starts from 40 minutes to 16 hours per day. The impact is in the form of a higher rate of weight gain, reduced need for parenteral nutrition, longer duration of breastfeeding, better immunological function and lung function, better sleep patterns, lower prolonged crying patterns, lower markers of stress in babies and mothers, and mortality rates. In the first month, it was quieter. In conclusion, skin-to-skin contact for LBW is safe to do from an early age, including for unstable LBW in the mild to moderate category; the duration starts from 40 minutes and is increased gradually according to the baby's tolerance and has been proven to have many positive impacts on both the baby and the mother. Keywords: LBW, Premature Babies, Kangaroo Method Treatment, Skin To Skin Contact